How international rents moderate business cycles’ relationship to high homicide rates - Leon, Daniel S. (Global crime, 2023)
I explore the relationships between macroeconomic conditions and how the forms of integration into the global economy affect homicide rates in 21 high-violence countries from 2000 to 2018. The analysis focuses on countries integrated into the global economy by accruing international economic rents. I use data from 2000 to 2018 to analyse how resource rents and remittances moderated the relationship between business cycles and high homicide rates. Moreover, I also evaluate how socioeconomic conditions mediate the above relationship. The results indicate that natural resource rents conditioned a procyclical relationship between business cycles and homicide rates. Contrastingly, remittances conditioned a countercyclical relationship between business cycles and homicide rates. The findings contribute to the rich and growing economic criminology and international political economy literature investigating how international rents condition subnational violence.